The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1002/ar.1092360319
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and histology of human accessory parotid glands

Abstract: The parotid glands of 228 Japanese human cadavers were examined to determine the incidence and histological features of accessory parotid glands. The incidence was found to be 56% with no differences between right and left sides or between sexes. Thirty parotid glands and their associated accessory glands were examined histologically: eight of these accessory glands were found to be mixed secretory glands (i.e., containing both serous and mucous acini). Thus, the pattern of differentiation of a significant fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 14 publications
(13 reference statements)
1
57
2
Order By: Relevance
“…1 The accessory parotid gland exists in 21-61% of individuals. [1][2][3] However the appearance of accessory parotid gland tumour is rare, with a reported frequency of 1-7.7%of all parotid gland tumours. 3,4 Generally, the tumour is asymptomatic initially, irrespective of the histological findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The accessory parotid gland exists in 21-61% of individuals. [1][2][3] However the appearance of accessory parotid gland tumour is rare, with a reported frequency of 1-7.7%of all parotid gland tumours. 3,4 Generally, the tumour is asymptomatic initially, irrespective of the histological findings.…”
Section: Discussionmentioning
confidence: 99%
“…The accessory parotid gland exists in 21-61% of individuals. [1][2][3] However, the appearance of an accessory parotid tumor is rare, with a reported frequency of 1-7.7% of all parotid gland tumours. 3 These small flat structures were once considered to be mere extension of the main parotid gland, but it is now known that they are independent glandular units with respect to their function and anatomic location.…”
Section: Introductionmentioning
confidence: 99%
“…The APG has a secondary duct emptying into Stensen's duct. Although the APG is seldom mentioned in the literature, it exists in 21-69% of individuals [1,10]. The incidence of APG tumors reportedly ranges from 1% to 7.7% [2,6].…”
Section: Discussionmentioning
confidence: 99%
“…Frommer 2 , in his study of cadaveric dissections, found an APG in 21% of individuals, although some authors reported incidences as high as 56% 3 . Although the APG is a common anatomical variation, APG tumours are extremely rare, with a reported incidence of 1 to 7.7% of all parotid gland tumours, and a malignancy rate from 26 to 50% 4,5 .…”
Section: Introductionmentioning
confidence: 98%